Polymetallic Complexes, Part XLVIII Complexes of Co(II), Ni((II), Cu(II), Zn(II), Cd(II) and Hg(II) with Chelating Bis-bidentate Donor Azodye Ligand. - B. Mahapatra, Bipin; Patel, Bhupal (Asian Journal of Chemistry, 2010)
Bis-bidentate chelating azodye ligand, 4,4´-bis[(acetylacetonyl-3´)-azol]-3,3´-dimethyldiphenyl form binuclear complexes with divalent metal ions. The Co(II), Cu(II) and Zn(II) complexes are found to be either octahedral or distorted octahedral, Ni(II) complex square planar and Cd(II) and Hg(II) complexes are tetrahedral as inferred from analysis, conductance, magnetic moments and spectral studies.